HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU MASYARAKAT TERHADAP KECEMASAN PENYEBARAN COVID-19 DI KECAMATAN SEPATAN TIMUR - Oktafilla, Bintang Maharani Putri; Herlia, Ide Chandra; Faridah, Ida (Nusantara Hasana Berdikari, 2021)
Background Covid-19 is a disease caused by a new type of Corona virus from Severe Acute Respiratory Syndrome (Sars-Cov-2) which was found in Wuhan, the capital city of Hubei Province, China at the end of 2019. The Covid-19 case in the East Sepatan District was cases confirmation of 270 souls. Research method in this study used a cross sectional approach. The population is the people of East Sepatan District with a population of 96,924 and a sample of 398 respondents is obtained. The sampling technique in this study was using quota sampling. Research result the p value of the level of knowledge and behavior is 0.000<0.05 while the result of the p value of the level of knowledge and anxiety is 0.000 <0.05 then Ha is accepted, meaning that there is a relationship between the level of knowledge and community behavior towards the anxiety of the spread of Covid-19 in East Sepatan District.